Investigation of factors determining risk-taking strategies in Pension fund investment of Defined Benefit schemes in the UK corporate pension system - Hu, Chunan (2014)
This paper investigates various incentives determining risk taking strategies of the corporate pension fund investment from the perspective of sponsors. In the United Kingdom, occupational pension plans especially defined benefit (DB) pension schemes play important roles in the financial market. Comparing with the conventional framework managing pension risk as a contained part of the whole firm risk, recent studies start to focus on pension risk especially investment risk as an individual topic and try to examine the determinants of the pension investment risk to find some effective solutions towards risk management of the pension fund investment. In this paper, in accordance with previous researches, several hypotheses about possible incentives determining the risk-taking strategies from sponsors have been tested and justified, namely, risk management, risk shifting, tax benefits, accounting effects and firm size effect hypotheses. Each of these hypotheses is measured by some related proxies such as funding ratios for the risk management and risk shifting hypotheses. As shown in the regression results, most of the hypotheses are proved to be consistent with previous hypotheses. Risk management hypotheses maintaining positive correlation between pension risk and funding ratios, tax benefits claiming negative coefficients of bonds ratio and firm size stating negative correlated relation are all confirmed by the actual results in this paper. Concerning risk transfer and accounting effect incentives which derive different results from the former hypotheses, possible reasons and limitations as influence from different stakeholders of different firms and different accounting regulations for the UK and the US or the technical limitations of the sample data has been clarified .